The Graphene/l-Cysteine/Gold-Modified Electrode for the Differential Pulse Stripping Voltammetry Detection of Trace Levels of Cadmium - Yu Song (Micromachines, 2016)
Cadmium(II) is a common water pollutant with high toxicity. It is of significant importance for detecting aqueous contaminants accurately, as these contaminants are harmful to human health and environment. This paper describes the fabrication, characterization, and application of an environment-friendly graphene (Gr)/l-cysteine/gold electrode to detect trace levels of cadmium (Cd) by differential pulse stripping voltammetry (DPSV). The influence of hydrogen overflow was decreased and the current response was enhanced because the modified graphene extended the potential range of the electrode. The Gr/l-cysteine/gold electrode showed high electrochemical conductivity, producing a marked increase in anodic peak currents (vs. the glass carbon electrode (GCE) and boron-doped diamond (BDD) electrode). The calculated detection limits are 1.15, 0.30, and 1.42 µg/L, and the sensitivities go up to 0.18, 21.69, and 152.0 nA·mm−2·µg−1·L for, respectively, the BDD electrode, the GCE, and the Gr/l-cysteine/gold electrode. It was shown that the Gr/l-cysteine/gold-modified electrode is an effective means for obtaining highly selective and sensitive electrodes to detect trace levels of cadmium.